Structural basis and mechanism for metallochaperone-assisted assembly of the Cu(A) center in cytochrome oxidase - Canonica, Fabia (Sci Adv, 2019)
The mechanisms underlying the biogenesis of the structurally unique, binuclear Cu(1.5+)•Cu(1.5+) redox center (Cu(A)) on subunit II (CoxB) of cytochrome oxidases have been a long-standing mystery. Here, we reconstituted the CoxB•Cu(A) center in vitro from apo-CoxB and the holo-forms of the copper transfer chaperones ScoI and PcuC. A previously unknown, highly stable ScoI•Cu(2+)•CoxB complex was shown to be rapidly formed as the first intermediate in the pathway. Moreover, our structural data revealed that PcuC has two copper-binding sites, one each for Cu(1+) and Cu(2+), and that only PcuC•Cu(1+)•Cu(2+) can release CoxB•Cu(2+) from the ScoI•Cu(2+)•CoxB complex. The CoxB•Cu(A) center was then formed quantitatively by transfer of Cu(1+) from a second equivalent of PcuC•Cu(1+)•Cu(2+) to CoxB•Cu(2+). This metalation pathway is consistent with all available in vivo data and identifies the sources of the Cu ions required for Cu(A) center formation and the order of their delivery to CoxB.